Music in Film: Film as Music - Mettler, Peter (Cinémas)

(untitled) (Cinémas, 1992)
Film and music hae the same communicative capacity, according to Toronto filmmaker Peter Mettler. By adopting the musical rhythms and procedures as creative vectors, the filmmaker, who is also the camaraman and the editor, acquires the means to produce a cinema of the unconscious, of the intuitive, either with or without a narrative structure. Mettler describes his musical approach to film and its application in three of his features: Scissere (1982), Eastern Avenue (1985), and The Top of His Head (1990).